Removal of methylene blue dye in aqueous solution by sorption on a bacterial-g-Poly-(Acrylic Acid) polymer network hydrogel - Adil Hakam,; I. Abdul Rahman,; M. Suzeren M. Jamil,; Rizafizah Othaman,; M.C.I. Mohamad Amin,; Azwan Mat Lazim, (Universiti Kebangsaan Malaysia, 2015)
In this study, Bacterial cellulose (BC) grafted with Acrylic acid (AA) was prepared using Co60 γ-rays source (30 KGy). Although many samples were prepared, BC: AA with ratio of 1:1 labelled as A1 and 2:1 labelled as A2 gave the most significant results. Hence these particular ratios have been selected and further investigated. AA was proven grafted onto BC by using ATR-FTIR due to the absent of C-O stretching (1040 cm-1) in both hydrogels. The SEM image of both hydrogels samples showed highly porosity networks structure have been produced. The physical properties of the hydrogels such as equilibrium water content (%) and swelling ratio (%) in different pH buffer solution were measured. It was found that the equilibrium water content (%) of A1 was 93.10% while A2 was 74.83%, respectively. The results indicated that the equilibrium water content (%) increased by gaining the AA concentration. At pH10, the A2 swelling ratio (%) was two folded with 3350% in comparison with the A1. For the removal of methylene blue (MB) from aqueous solution, the results from the UV-VIS spectroscopy demonstrated that the A2 sample hydrogel was also an effective absorbent material.